2015
DOI: 10.1016/j.compenvurbsys.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spatial segregation and travel cost influences on utilitarian walking: Towards policy intervention

Abstract: We develop an agent-based model of utilitarian walking and use the model to explore spatial and socioeconomic factors affecting adult utilitarian walking and how travel costs as well as various educational interventions aimed at changing attitudes can alter the prevalence of walking and income differentials in walking. The model is validated against US national data. We contrast realistic and extreme parameter values in our model and test effects of changing these parameters across various segregation and pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Ultimately a series of complementary approaches including observational studies like the MESA Neighborhood Study, policy evaluations, and simulation modeling will be necessary to identify effective neighborhood interventions to improve cardiovascular health. [102]…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately a series of complementary approaches including observational studies like the MESA Neighborhood Study, policy evaluations, and simulation modeling will be necessary to identify effective neighborhood interventions to improve cardiovascular health. [102]…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic processes and causal relationships could be explicitly implemented in an ABM to test hypotheses, make predictions, or explore policy interventions 130,131 . For example, an ABM has been developed to examine the influence of spatial segregation and travel cost influences on utilitarian walking 132 . In this model, travel mode choice is based on a utility function that incorporates travel cost and attitude towards each travel mode.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, we observed an equally slight reduction in the annual prevalence of violent victimization from implementing either hot-spot policing for 10 years or increasing CBT by 100% for 30 years; however, the joint implementation of hot-spot policing and a 50% increase in CBT resulted in a similar reduction in just five years. Our observation that interventions can work synergistically to obtain optimum improvement in population health has been replicated across several similar studies that have employed systems science methods [57, 46, 33, 47, 59]. Because the development, implementation, and long-term evaluation of community health interventions can be costly, ABMs have provided a particularly attractive opportunity to sequentially evaluate several competing interventions to determine those most likely to provide population health benefits.…”
Section: Case Study: the Role Of System Science In Evaluation Of The mentioning
confidence: 79%
“…Yang and colleagues employed an ABM to simulate several structural interventions that could target the walking behaviors of both school-aged children [30, 31] and adults [32, 33]. Interventions ranged from improving traffic safety [30, 31] to reducing residential segregation [33]. These simulations showed that the impact of the interventions depended on the changes in behavior it produced in the local social network.…”
Section: Methodological Contributionsmentioning
confidence: 99%